Extreme rejuvenation and softening in a bulk metallic glass - J. Pan (Nature Portfolio, 2018)
Deforming metallic glasses can rejuvenate them to higher energy states, but only in the shear bands where deformation is usually concentrated. Here, the authors use a notched setup to suppress shear banding and promote significant bulk softening of a zirconium-based metallic glass.